Penerapan Hukum Adat Suku Dani Pada Perkawinan Perempuan di Bawah Umur di Kabupaten Jayawijaya - jprautor, jprautor (Fakultas Hukum Universitas Kanjuruhan Malang, 2015)
Since human beings are born into the world already have a tendency to live together with other human beings in a social life. in the smallest form, it starts living together with a family. Where in the family symptoms of human life will be formed at least by a man and a woman. Living together between a man and a woman who has met the requirements is called marriage.Formulation of the problem in this study were: (1) How does the application of customary law Dani in Jayawijaya against girls under the age of marriage?; (2) How to cope with efforts to suppress the occurrence of marriage underage girls?Research using empirical juridical approach, since this approach Directly describe the facts that occurred in the field and examine regarding berlakunnya customary law and national law in society Dani, Jayawijaya District.In the positive law is set up on the law of marriage, but the growing problem of marriage result in a conflict between the facts on the ground with customary law and positive law. State laws governing marriage is Law 1 Year 1974. But customary law governing marriage from the beginning until now has not changed in contrast to the positive law. If you look from the beginning where the laws in our country today were born because of the customary marriage law. Of the existence of this age limit can be interpreted that the Law No. 1 of 1974 does not require the implementation of underage marriage that has been set by Act No. 1 of 1974.Efforts to suppress the application of tackling common law marriage Dani on underage girls in Jayawijaya. Jayawijaya District Government repeatedly tried to approach the chiefs and the heads of the village so that they unite and work together to press the community Dani who always marry or marry underage girls, supayah with this partnership Dani society can change their mindset that this selamah thought wrong, and marry underage girls because, according to government and church leaders Son as part of the younger generation is the successor to the ideals of national struggle once human capital for national development